(untitled) (Bangladesh Medical Journal, 2010)
Pregnancy in non-communicating rudimentary horn is extremely rare. It carries grave risk to mother and fetus due to rupture of rudimentary horn in second trimester of pregnancy. Here is a case of ruptured rudimentary horn pregnancy at gestation of 14 weeks. Laparotomy was done and the rudimentary horn was excised. Postoperative recovery was uneventful. Keywords: Two unicornuate uteruses; rudimentary horn; rupture DOI: 10.3329/bmj.v39i1.6234 Bangladesh Medical Journal 2010; 39(1): 47-48